Geomodels in engineering geology : an introduction - Fookes, Peter (Whittles Publishing, 2015)
This book provides a valuable systematic guide to the evaluation and understanding of worldwide ground and environmental conditions of sites and their surrounds.
Keywords: Engineering geology.; elektronické knihy; electronic books